El mecanismo de Asociaciones Público Privada como posibilidad de inversión en infraestructura en la Región San Martín. Periodo 2016 - Benavides Gonzales, Yeeseña Marisol (2016)
The aim of this research is "Explain the mechanism of Public Private Partnerships in relation to infrastructure through the techniques of the survey and document analysis as investment possibility in the San Martin region. 2016 period. “This objective responds positively to the main problem formulated in the negative and that stems from the problematic reality. The methodology used part of the selection of a sample aspirational or convenience, which is comprised of a total of 35 people, who make up the senior management and management of the Regional Government that are linked to the subject under study. The research is applied in the Explanatory level and the design of it is not experimental by using inductive-deductive and analytical method - synthetic as well as techniques and instruments for data collection using the survey and document analysis, proceeded processing and data analysis for the testing of the hypothesis. The results of the research, descriptive and explanatory and discussion of these results shows that the mechanism of Public Private Partnerships is a real possibility for infrastructure investment in the San Martin region. 2016 period